CRISPR-Cas9: A method for establishing rat models of drug metabolism and pharmacokinetics - Jian Lu; Jie Liu; Yuanqing Guo; Yuanjin Zhang; Yeye Xu; Xin Wang (Elsevier, 2021)
The 2020 Nobel Prize in Chemistry recognized CRISPR-Cas9, a super-selective and precise gene editing tool. CRISPR-Cas9 has an obvious advantage in editing multiple genes in the same cell, and presents great potential in disease treatment and animal model construction. In recent years, CRISPR-Cas9 has been used to establish a series of rat models of drug metabolism and pharmacokinetics (DMPK), such as Cyp, Abcb1, Oatp1b2 gene knockout rats. These new rat models are not only widely used in the study of drug metabolism, chemical toxicity, and carcinogenicity, but also promote the study of DMPK related mechanism, and further strengthen the relationship between drug metabolism and pharmacology/toxicology. This review systematically introduces the advantages and disadvantages of CRISPR-Cas9, summarizes the methods of establishing DMPK rat models, discusses the main challenges in this field, and proposes strategies to overcome these problems.